Preparation, characterization and chemical modification of graphene based polypropylene nanocomposites - Nur Hidayah Md Said (Institute of Nano Electronic Engineering (INEE), Universiti Malaysia Perlis, 2019)
The development of MWCNT integrated BGFET for protein biosensor has been divided into five different stages. For the first step, the BGFET device was fabricated from SOI substrate using conventional photolithography, reactive ion etching (RIE) and electrode deposition process. The fabricated BGFET will function as a sensor for biomolecules interaction. Second stage discussed on the functionalization and characterization of MWCNT. MWCNT has been functionalized first before integration. Surface characterization has been conducted to verify the presence of desired functional groups. The functionalized MWCNT will be further used as biomolecules immobilization site.